Cover Image, Volume 16, Issue 1. Issue 1 (8th January 2022) - Unknown
Abstract : On the cover : Researcher Teclemariam Weldekidan in front of a series of two‐row plots of selected generations from the tropical synthetic of maize (the Delaware lineage). See T. Weldekidan et al., "Registration of tropical populations of maize selected in parallel for early flowering time across the United States, " https://doi.org/10.1002/plr2.20181 . Photo by University of Delaware.